BAWASLU's Efforts to Overcome the Practice of Money Politics in Tanjungpinang City - Asif Rizky Romadhon; Muhammad Pikri; Jaka Irwandi (Formosa Journal of Applied Sciences, 2023)
This study aims to determine the efforts of BAWASLU Tanjungpinang City in overcoming the practice of money politics in the Tanjungpinang City area. In this study, researchers used a descriptive qualitative approach. The results of this study show that the efforts of BAWASLU Tanjungpinang City in overcoming the practice of money politics are divided into three efforts in accordance with laws and regulations. First, BAWASLU Tanjungpinang City recapitulates an area that is potentially prone to money politics. Second, BAWASLU mobilizes supervisory personnel, political parties, and related organizations in tackling the spread of money politics. Third, BAWASLU Tanjungpinang city will follow up on allegations of money politics in the election constitutionally until proven and sanctioned by the authorities.